(untitled) (Jurnal Simki Economic, 2023)
The ever-increasing competition in the business world requires every company to adopt specific strategies to stay in business. This method of research is descriptive field research, that is, research aimed at providing an overview of specific details of a situation, social environment, or human relationship. We use secondary data from the Indonesia Stock Exchange. The samples were his five-year financial reports namely PT Indofood Sukses Makmur Tbk, PT Garudafood Putra Putri Jaya Tbk and Indofood CBP Sukses Makmur Tbk 2018-2022 financial reports. Data collection methods that involve documentation methods, i.e. data collection methods collected from records and documents related to the study. Data analysis techniques were performed quantitatively using the Altman Z-score method. After calculating the Z-score ratio = 6.56 x 1 + 3.62 x 2 + 6.72 x 3 + 1.05 x 4. Calculations and analysis of the company’s financial performance indicated a deterioration in its financial position, which was not material to PT. Garuda Food Putra Putri Jaya Tbk and PT. Indofood Sukses Makmur Tbk. On the other hand, PT Indofood CBP Sukses Makmur Tbk from 2018 to 2022 has deteriorated but remains in the safe range or healthy. This can be seen trending for PT Indofood CBP Sukses Makmur, Tbk. The lowest Z-score is 3.05.